2015
DOI: 10.1016/j.cardfail.2014.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Association of Antidiabetic Medications Targeting the Glucagon-Like Peptide 1 Pathway and Heart Failure Events in Patients With Diabetes

Abstract: Background Glucagon-like peptide-1 (GLP-1) agonists and dipeptidyl peptidase-4 (DPP-4) inhibitors (GLP-1 agents) may be protective in heart failure (HF). We set out to determine whether GLP-1 agent use is associated with HF risk in diabetics. Methods and Results Retrospective cohort study of members of a large health system. We identified >19,000 adult diabetics from January 1, 2000–July 1, 2012. GLP-1 agent users were matched 1:2 to controls using propensity matching based on age, race, gender, coronary dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 34 publications
0
49
0
1
Order By: Relevance
“…Prior observational studies (12,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) that assessed the association between hHF and either the DPP-4i agents as a class or specific DPP-4i agents (i.e., sitagliptin) have used a wide variety of designs and patient populations with mixed results. Two studies (12,18) identified that DPP-4i treatment is associated with a reduced rate of hHF relative to other oral antihyperglycemic medications, two studies (14,16) suggested a neutral association relative to other oral antihyperglycemic medications and/or insulin, and two studies (19,20) suggested an increased rate of hHF with DPP-4i treatment relative to matched control subjects not otherwise initiating a new antihyperglycemic medication but rather in the midst of treatment with any of a range of potential antihyperglycemic medications. Notably, the designs used by the two studies that found an association between the DPP-4i treatment and an increased rate of heart failure may have created a risk of residual bias in favor of the matched control subjects; all else being equal, the matched patients did not necessarily require new pharmacotherapy to manage their diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Prior observational studies (12,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) that assessed the association between hHF and either the DPP-4i agents as a class or specific DPP-4i agents (i.e., sitagliptin) have used a wide variety of designs and patient populations with mixed results. Two studies (12,18) identified that DPP-4i treatment is associated with a reduced rate of hHF relative to other oral antihyperglycemic medications, two studies (14,16) suggested a neutral association relative to other oral antihyperglycemic medications and/or insulin, and two studies (19,20) suggested an increased rate of hHF with DPP-4i treatment relative to matched control subjects not otherwise initiating a new antihyperglycemic medication but rather in the midst of treatment with any of a range of potential antihyperglycemic medications. Notably, the designs used by the two studies that found an association between the DPP-4i treatment and an increased rate of heart failure may have created a risk of residual bias in favor of the matched control subjects; all else being equal, the matched patients did not necessarily require new pharmacotherapy to manage their diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Effects on hospital admission for heart failure All five trials 9 evidence from observational studies Of 12 observational studies, four [109][110][111][112] reported heart failure, and eight 13-17 113-115 reported hospital admission for heart failure; nine 13-15 109-111 [113][114][115] were cohort studies and the other three 16 17 112 were nested case-control studies (fig 1). Observational studies reporting heart failure Of the four studies reporting heart failure, two prospective cohort studies 109 (table 4 and table 5).…”
Section: Trials Reporting Hospital Admission For Heart Failurementioning
confidence: 99%
“…Effects on hospital admission for heart failure All but one retrospective cohort study 115 reported unadjusted rates of hospital admission for heart failure. The five cohort studies 13 to imprecision *Most trials had unclear risk of bias on random sequence generation and allocation concealment (web appendix 2), and the follow-up (median of 52 weeks) was not long enough for heart failure to occur in patients at low risk of cardiovascular disease.…”
Section: Effects On Heart Failurementioning
confidence: 99%
“…Without the inclusion of data from this trial, data on increased risks associated with DPP-4 inhibitor use are insufficient, and real-world observational studies are needed to address this knowledge gap. Some previous observational studies have suggested the patients with T2DM receiving incretin-based regimens were at increased risk of hospitalisation for HF,23 24 whereas other studies have found no such association25–27 or even a decreased risk of hospitalisation 28 29. However, only one of these studies focused on patients with pre-existing HF 24.…”
Section: Discussionmentioning
confidence: 99%